2016
DOI: 10.1111/hdi.12515
|View full text |Cite
|
Sign up to set email alerts
|

Dialytic hemodynamics are associated with changes in gait speed

Abstract: Introduction Functional impairment and reduced mobility are prevalent in patients on chronic hemodialysis (HD). The impact of HD on physical performance and mobility needs evaluation. Methods We measured gait speed in a cohort of chronic HD patients both pre and post an HD session. We collected demographic and laboratory data and dialytic hemodynamic parameters for the HD session. Participants completed the Falls Efficacy Scale International (FES-I) survey to assess concern for falling. We used linear regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Several older adults receiving HD in our study cited HD treatments as acutely worsening their mobility. Although we did not quantitate mobility before and after HD treatments, Wolfgram et al 21 found that gait speeds decreased by 0.06 m/s shortly after a HD session, which is a clinically meaningful change in older adults. 27 In this study, they found that changes in gait speed after HD were associated with the magnitude of systolic and diastolic blood pressure changes during HD.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Several older adults receiving HD in our study cited HD treatments as acutely worsening their mobility. Although we did not quantitate mobility before and after HD treatments, Wolfgram et al 21 found that gait speeds decreased by 0.06 m/s shortly after a HD session, which is a clinically meaningful change in older adults. 27 In this study, they found that changes in gait speed after HD were associated with the magnitude of systolic and diastolic blood pressure changes during HD.…”
Section: Discussionmentioning
confidence: 73%
“…In 37 older adults receiving HD, Hall et al 18 found that the mean SPPB score was 6 points, and Chen et al 19 demonstrated that the median SPPB score was 5 points in 50 older adults receiving HD. For gait speed, Zhou et al 20 found that among 36 older adults receiving HD with diabetes, the mean gait speed was 0.4 m/s, and Wolfgram et al 21 found that the mean gait speed before initiating a dialysis treatment was 0.76 m/s in 28 older adults receiving HD. In comparison, the younger participants of the Frequent Hemodialysis Network Trial, 22 who had a mean age of 50.7 years, had a mean SPPB score of 8.5 points at enrollment.…”
Section: Discussionmentioning
confidence: 99%
“…The fluid overload significantly impacts on the physical performance of the patients over time, as observed in a longitudinal study by Carlos et al (12). On the other hand, excessive fluid withdrawal in hemodialysis sessions can lead to intradialytic hypotension, which is associated with a reduced gait after a dialysis session (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…We consistently timed our gait speed and grip strength measures pre- or post-dialysis within individual subjects. This is important since there are changes in gait speed with a single dialysis session, dependent on dialysis run hemodynamics [44]. A limitation of the study is that gait speed was measured post dialysis for the 1st shift subjects (36%) but prior to dialysis session in the rest.…”
Section: Discussionmentioning
confidence: 99%